Obstetric outcomes of vaginal birth after caesarean section in Bingham University Teaching Hospital, Jos, Nigeria - Edugbe, Adikpe E.; Bitus, James; Nnawike, Okeke C.; John, Onyeji; Mikah, Samaila (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Objective of the study was to review the obstetric outcomes of vaginal birth after caesarean section (VBAC) in Bingham University Teaching Hospital (BhUTH). Methods: A retrospective review of women planned for VBAC at BhUTH from January, 2020 to December 2021. Variables measured included gestational age at time of delivery, inter-delivery interval, and vaginal delivery before or after primary caesarean section (CS), outcome of labor, indications for repeat CS, neonatal and maternal outcomes. Results: During the study period there were 1535 deliveries and 94 were planned VBAC. Of the 94, 55.3% had a repeat emergency CS while 44.7% had a successful VBAC. Successful VBAC rate was 52.4% in multipara compared to 47.6% in primipara. Repeat CS rate was 34.6% in multips and 65.4% in primaparas. The commonest indication for the repeat CS was failure to progress due to cephalopelvic disproportion, 26.9%, mal-positioning, 25.0%, fetal distress and poor uterine contractions accounted for 13.5% each. Prior vaginal delivery especially a prior VBAC was associated with a higher rate of successful VBAC, 40.5% compared to VBAC rate of 21.4% in those who had a vaginal delivery before the caesarean section. The successful VBAC rate was highest among those weighing 2.5<3.5 kg, 66.7% compared to fetal weight of <2.5 kg and ≥3.5 kg birth weight. Conclusions: The VBAC rate observed is higher than what is obtainable in other centers in our country but is far less than what is obtainable in the developed societies. The maternal and perinatal morbidity and mortality are however comparable with the developed societies despite our limited facilities.